JunB is essential for IL-23-dependent pathogenicity of Th17 cells - Zafrul Hasan (Nature Portfolio, 2017)
T helper 17 (Th17) cells can be pathogenic, but what controls this phenotype is unclear. Here the authors show that the transcription factor JunB promotes proinflammatory Th17 function by regulating the transcription of multiple Th17-related genes.